2018
DOI: 10.3991/ijim.v12i4.9203
|View full text |Cite
|
Sign up to set email alerts
|

Motivation of 14 Year-old Students using Tablets, compared to those using Textbooks and Workbooks

Abstract: Intrinsic motivation is important and it can be divided in different dimensions. The Self-Determination Theory is based on intrinsic motivation. The test based on this theory was given to 14-year old students from three different schools: one where students used tablets in the science class during the 2015-16 school year, and two schools where students used textbooks and workbooks for the same subject in the classroom and at home. The test measured three dimensions of intrinsic motivation: interest and satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
1
6
0
5
Order By: Relevance
“…El Test de motivación intrínseca (IMI) se ha utilizado con éxito en varios estudios que miden la autorregulación y la motivación intrínseca (Deci y Ryan, 2008), entre ellos su validez fue confirmada por McAuley et al (1989). Además, es un test ampliamente utilizado en estudios de motivación para medir el efecto de herramientas tecnológicas (Mendez y Sota, 2017;Mendez et al, 2018). Para los fines de este estudio, se utilizó una encuesta administrada a través de los formularios de Google.…”
Section: Metodologíaunclassified
“…El Test de motivación intrínseca (IMI) se ha utilizado con éxito en varios estudios que miden la autorregulación y la motivación intrínseca (Deci y Ryan, 2008), entre ellos su validez fue confirmada por McAuley et al (1989). Además, es un test ampliamente utilizado en estudios de motivación para medir el efecto de herramientas tecnológicas (Mendez y Sota, 2017;Mendez et al, 2018). Para los fines de este estudio, se utilizó una encuesta administrada a través de los formularios de Google.…”
Section: Metodologíaunclassified
“…Their collective findings reported that the application of technology in education could improve student anger management skills, enhance the teaching-learning process's effectiveness, increase academic achievement, and foster positive behavior [7][8][9][10][11][12][13]. Other studies presented that the application of technology can raise problem-solving capability, heighten computational thinking competency, upgrade writing ability, be adopted due to usefulness and easiness, and boost motivation [14][15][16][17][18][19]. The advantages of using technology in education in the cognitive and affective domain are seen in the current studies` interests.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, Intrinsic Motivation Inventory (IMI) was used to know the participants’ motivation. This test has been used in many investigations at different times, from people of different ages ( Eskeles, 1982 ; Mendez et al, 2018 ; Heilat and Seifert, 2019 ), or even professors as in the present investigation ( Demir, 2011 ; Liu et al, 2019 ). Teachers may be exposed to external and internal motivation.…”
Section: Introductionmentioning
confidence: 99%